Investigation of flexible bellow for cooling isolated electronic components - Zheng, Yun. (2009)
The present work investigates the method of indirect liquid cooling employing a flexible bellow liquid heat sink sandwiched between two hot plates in electronic package. The scope of the project includes the formulation and development of a vertically averaged 2-D numerical model to simulate the heat and fluid flow phenomena in the bellow. The numerical model applies the finite volume method on a staggered grid. Solutions are obtained using the TDMA (TriDiagonal-Matrix Algorithm) and pressure-velocity correction technique. The numerical model is assessed by experimental work in a previous study and is found to be in fair agreement.